Deficits, debt, and democracy : wrestling with tragedy on the fiscal commons - Wagner, Richard E. (Cheltenham : Edward Elgar, 2012)
This timely book reveals that the budget deficits and accumulating debts that plague modern democracies reflect a clash between two rationalities of governance: one of private property and one of common property. The clashing of these rationalities at various places in society creates forms of societal tectonics that play out through budgeting. The book demonstrates that while this clash is an inherent feature of democratic political economy, it can nonetheless be limited through embracing once again a constitution of liberty.
1. Budgeting: The Elusive Quest for Fiscal Responsibility -- 2. Budgeting and Political Economy: A Theoretical Framework -- 3. Budget Deficits, Ricardian Equivalence, and Macro-micro Supervenience -- 4. Property Rights, Societal Tectonics, and the Fiscal Commons -- 5. Parliamentary Assemblies as Peculiar Market Bazaars -- 6. Taxation, Fiscal Politics, and Political Pricing -- 7. Regulation as Alternative Taxation -- 8. Public Finance for a Constitution of Liberty.
Includes bibliographical references and index.
Keywords: Budget deficits; Debts, Public; Fiscal policy; Democracy -- Economic aspects